2016
DOI: 10.14786/flr.v4i3.182
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among motivation, commitment, cognitive capacities, and achievement in secondary education

Abstract: The aims of the present study were (1) to identify to what extent school motivation and school commitment contributed to the explanation of students' academic achievement in addition to the effect of students' cognitive capacities, (2) to find out whether school commitment mediated the relation between school motivation and academic achievement, and (3) to find out whether school motivation mediated the relation between school commitment and academic achievement. New in the field is that perspectives from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
4
1
3
Order By: Relevance
“…Neither explicit nor implicit motivation was significantly associated with behavioural engagement, contrary to previous studies (Green et al, 2012;Korpershoek, 2016;Michou et al, 2014;Taylor et al, 2014;Walker, et al, 2006). Previous studies typically used self-reports to assess both explicit motivation and behavioural engagement and found more substantial correlations between explicit motivation and behavioural engagement.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Neither explicit nor implicit motivation was significantly associated with behavioural engagement, contrary to previous studies (Green et al, 2012;Korpershoek, 2016;Michou et al, 2014;Taylor et al, 2014;Walker, et al, 2006). Previous studies typically used self-reports to assess both explicit motivation and behavioural engagement and found more substantial correlations between explicit motivation and behavioural engagement.…”
Section: Discussioncontrasting
confidence: 82%
“…Self-determination theory (SDT) (Deci & Ryan, 1985;Ryan & Deci, 2000a) states that intrinsic motivation facilitates higher levels of engagement and achievement, whereas extrinsic types of motivation can lead to maladaptive learning behaviours and outcomes. Previous research has empirically supported these claims and found positive reciprocal associations between intrinsic motivation and engagement and achievement (see for example Green et al, 2012;Guay, Ratelle, Liem, & Litalien, 2010;Korpershoek, 2016;Michou,Vansteenkiste, Mouratidis, & Lens, 2014;Taylor et al, 2014;Walker, Greene, & Mansell, 2006). Even though motivation has been found to facilitate achievement and vice versa, most studies only found weak or modest associations between motivation-related constructs on the hand, and behavioural engagement and achievement on the other hand (for reviews, see for example Cerasoli, Nicklin, & Ford, 2014;Richardson, Abraham, & Bond, 2012) instead of the powerful relationships that are often assumed.…”
Section: Introductionmentioning
confidence: 90%
“…The most commonly used definition of school belonging is by Goodenow (1993): "The extent to which students feel personally accepted, respected, included and supported in the school social environment". Korpershoek (2016) claims that students have a pervasive drive to form and maintain significant interpersonal relationships with their teachers and peers and a psychological need to create ties to the school as an institution. Belonging and connectedness with same-aged peers and adult figures outside the family, such as teachers, may hold particular importance as adolescents begin to transfer their dependencies from parents and families to extra-familial contexts (Allen, 2008;Österman, 2000;Demanet & Van Houtte, 2012).…”
Section: Sense Of Belonging In the School And Classroommentioning
confidence: 99%
“…This means that people tend to internalise values and practices from contexts (and people within that context) in which they experience a sense of belonging (Niemiec and Ryan 2009). Within the school context, as explained in Korpershoek (2016), following both the belongingness hypothesis as well as SDT, students generally have a pervasive drive (or in SDT an innate need) to form and maintain significant interpersonal relationships (e.g. with their teachers and peers) and a psychological need to create ties to the school as institution.…”
Section: School Belongingmentioning
confidence: 99%